POTENSI SOSIAL BUDAYA MASYARAKAT BAGI PEMBANGUNAN KESATUAN PENGELOLAAN HUTAN (KPH) PADA WILAYAH KPH MODEL SINTUWU MAROSO DI DESA TAMBARANA KECAMATAN POSO PESISIR UTARA - Moyo, Maya Irma Dewi; Golar, Golar; Rukmi, Rukmi (Warta Rimba, 2013)
Model FMU management plan Sintuwu Maroso as one model of community -based forest utilization . This is also expected through community access to forest areas. Thus the public will be more empowered and able to improve the ability, in using the natural resources optimally. But to realize it needed information about the potential and prospects, which is the social and cultural potential in supporting the development in the FMU Model Sintuwu Maroso. The research was conducted in the Tambarana village. Specified site intentionally (purposive sampling), with the main consideration, this village is one of the villages that fall within the area development model Sintuwu Maroso KPH. Analysis of the data is a descriptive analysis. From the results, it can be concluded as follows, that Socio-cultural potentials that exist in the Tambarana village, may indirectly support the Forest Management Unit (FMU) Sintuwu Maroso, Tambarana Village Community also has the potential to be social and cultural customs handed down through generations in terms of land use, the community formed a Land Control Team, and Other socio- cultural potential, characterized by harmonious relationships between residents and village rules made ââto prevent the emergence of the conflict, one of which was the establishment of the FKUB. Key Words : sosio-cultural, Forest Management Unit